2021
DOI: 10.1186/s13052-021-01154-w
|View full text |Cite
|
Sign up to set email alerts
|

Under-nutrition and associated factors among children on ART in Southern Ethiopia: a facility-based cross-sectional study

Abstract: Background Malnutrition is very common in HIV-infected individuals. Even though data from different settings are necessary to tackle it, pieces of evidence are limited especially in the case of the nutritional status of HIV-infected children. Hence, this study aims to assess the nutritional status and associated factors among children on antiretroviral therapy. Methods An institutional-based cross-sectional study was conducted among 383 HIV-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Our study showed that nearly half (49.1%) of HIV-positive children were stunted. This prevalence was higher than that reported from other studies in Adama, Amhara region, and a previous study in Southern Ethiopia ( 32 , 33 , 36 ). Researches indicated that children were disproportionately affected in environments where there is conflict ( 37 , 38 ).…”
Section: Discussioncontrasting
confidence: 72%
“…Our study showed that nearly half (49.1%) of HIV-positive children were stunted. This prevalence was higher than that reported from other studies in Adama, Amhara region, and a previous study in Southern Ethiopia ( 32 , 33 , 36 ). Researches indicated that children were disproportionately affected in environments where there is conflict ( 37 , 38 ).…”
Section: Discussioncontrasting
confidence: 72%
“…This systematic review and meta-analysis included 38 primary articles with a total of 16,790 study participants published between 2010 and 2021 from more than 16 sub-Saharan African countries [ 6 – 8 , 22 – 27 , 33 – 61 ] (Table 1 ). All primary studies included in this systematic review and meta-analysis were observational studies conducted in health facilities with a sample size 28 to 3195 from study conducted in South Africa [ 48 ] and West Africa [ 46 ] respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The highest prevalence of stunting was reported from a study conducted in Cameron (77.0%) [ 23 ], and the lowest was reported from a study conducted in Ethiopia (5.5%) [ 61 ]. Similarly, the highest prevalence of underweight was reported from a study in Nigeria (58.6%) [ 7 ], and the lowest was from a study in Tanzania (6.8%) [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The full texts of 62 articles were downloaded and assessed against inclusion criteria. Thus, 18 articles were excluded for the following reasons: 7 studies did not report data on the outcome variable [5,[24][25][26][27][28][29], six studies were review papers [4,14,[30][31][32][33], three studies focused on children [30,34,35], one study was conducted out of SSA [36], one study focused on pregnant women [37], and one study lacks full text [38]. Finally, 44 studies were included in final systematic review and meta-analysis (Fig 1) [23].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%